The Potential of Distance Learning within the Course “History of Linguistic Studies” - Lukyanenko, Sergiy (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2024)
The transformation of the educational space at the beginning of the 21st century involves the further improvement of academic disciplines and students' competencies. The distance learning system (DLS) Moodle provides new opportunities for this.The purpose of the article is the formation of scenarios for using the potential of the DLS Moodle using the example of the distance learning course "History of Linguistic Studies".The realization of the potential of DLS is related to the structuring of educational information, the analysis of tasks and the content of a specific discipline. The purpose of the special course "History of Linguistic Studies" is to acquaint philologists with the evolution of linguistic science. The specificity of the distance course provides for the placement of educational and informational content in several blocks (parts). The main attention is paid to the substantive part, the basic elements of which are "Lecture", "Seminar session", "Main Forum" and "Additional Forum". Lecture information is accompanied by additional sources: presentations, videos, scientific publications, etc. Independent work and ongoing control are organized within seminar classes and forums. Seminar classes take place in classroom and/or correspondence formats. A specific component of DLS are forums, participation in which involves creating an essay on a certain aspect of the topic. In the main forums, several "basic" aspects are brought up for discussion; additional ones relate to issues qualified as optional. The formation of student autonomy involves participation in improving the course under the guidance of a teacher-moderator. This activity includes: creation of presentations, reasoned analysis of presentations of fellow students, discussion of the analysis of presentations and making appropriate corrections. In this way, indirect work takes place with the maximum possible range of topics.The course has potential for improvement in the direction of organizing seminars and forums, as well as monitoring the content used by students. The acquired experience can be used in the creation and improvement of distance courses in other disciplines of the linguistic cycle of higher philological education.